Discourse, policy and the environment: hegemony, statements and the analysis of U.K. airport expansion. Issue 5 (3rd September 2019) - Griggs, Steven; Howarth, David
ABSTRACT: Building on the work of Laclau and Mouffe and others, this article develops a distinctively poststructuralist approach to the analysis of policy discourse in the field of environmental politics. Despite advances, there remain persistent critiques of the approach. Some claim that its theoretical assumptions are either too ideational or insufficiently attuned to the linguistic aspect of discourse analysis. Others pinpoint methodological difficulties in operationalizing the approach and generating effective research strategies. Addressing such critiques, we seek to articulate elements of Laclau and Mouffe's post-Marxist theory of hegemony with insights gleaned from Foucault's archaeology of discourse, more specifically his idea of the statement. When supplemented with the logic of hegemony, we argue that describing and mapping statements of various types, as they appear and disappear, circulate and change, in relation to particular policy problems in specific historical contexts, provides vital clues for delimiting competing discursive formations. It also enables researchers to detect and explicate the underlying rules that made them possible and brought them into being. We illustrate such claims through an empirical analysis of three exemplary statements in aviation policy in the United Kingdom, demonstrating how the critical evaluation of these statements offers a lens through which to examine the continuities and discontinuities of on-going hegemonic struggles.